Aplikasi Kurikulum pada Layout Ruang Kelas Preschool Surabaya Grammar School (SGS) - Setiono, Melisa (Intra, 2013)
Golden age period is a period where children between age 2 until 6 years old increasing their psychology, physical, and brain development in maximum. In this preiod children can recieve information as much as possible. One of tool that can help children is preschool. Preschool itself is a tool for learning and playing for children. Preschool has a curriculum be in the form learning method to support learning process. Beside that, preschool has to have a good environment school. One of the effort is by applying curriculum into the classroom layout. The goal of this reseacrh is knowing how curriculum be applied to classroom layout in Surabaya Grammar School (SGS) preschool. As for results of the conclussion from this research, curriculum is not only be applied to learning method only, but in classroom layout too to support childâs needs.